Lost in Translation: George Eliot’s and Andrew Davies’ Daniel Deronda(s) - Neufeld, Hannah (Revue CMC Review, 2019)
Hannah Neufeld’s essay compares George Eliot’s 1876 novel, Daniel Deronda, to a film adaptation by Andrew Davies. Eliot’s novel draws an analogy between the situation of women and that of the often marginalized Jewish community in Victorian England, with their dream of a promised land.